Optically-Pumped Single-Mode Deep-Ultraviolet Microdisk Lasers With AlGaN-Based Multiple Quantum Wells on Si Substrate - Yiyun Zhang; Hongjian Li; Panpan Li; Arash Dehzangi; Liancheng Wang; Xiaoyan Yi; Guohong Wang (IEEE Photonics Journal, 2017)
In this work, we report demonstration of optically-pumped single-mode deep-ultraviolet lasing actions operating at room temperature from ∼1-μm 150-nm-thick undercut microdisks with AlN/Al0.35Ga 0.65N (5.5 nm/2.5 nm) multiple quantum wells. These AlGaN-based microdisks are grown on Si substrate by metal-organic chemical vapor deposition. The lasing wavelength centers at ∼300.1 nm with the linewidth of ∼1.0 nm as the excitation exceeds the lasing threshold of ∼24.2 mJ/cm2. An emission coupling factor (β) of 9.2 × 10−2 is estimated based on the light output characteristics of the AlN/AlGaN microdisks with increasing the pumping densities. Concurrently, a 100 meV blue-shift in the mode energy has also been observed. The lasing spectral peak is attributed to fundamental-order transverse-electric whispering-gallery modes, confirmed by three-dimensional finite-difference time-domain simulations.